How Do Interest-Only Mortgages Affect Consumption and Saving over the Life Cycle? - Larsen, Linda Sandris; Munk, Claus; Nielsen, Rikke Sejer; Rangvid, Jesper (Management Science, 2024)
Using a unique data set with detailed information on Danish households and their mortgages, we show that young and old households are more likely to use interest-only (IO) mortgages compared with middle-aged households. Young households use IO mortgages because they expect higher future income and old households because IO mortgages allow them to circumvent an otherwise binding liquidity constraint. Through different channels, IO mortgages thus facilitate consumption smoothing for young and old households. Our detailed data also allow us to examine how households with IO mortgages differ from households with repayment mortgages in terms of leverage, debt and asset composition, and pension contributions. This paper was accepted by Tomasz Piskorski, finance. Funding: All authors gratefully acknowledge support from the Danish Finance Institute. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.4787 .